Personal Branding for tennis coaches - van Dijk, Youvale (ITF Coaching & Sport Science Review, 2015)
This article identifies the need for personal branding in one’s career – a phenomenon that has gained importance in recent years. By establishing a personal brand coaches are able to differentiate themselves. Four key steps in establishing a personal brand are identified: self-assessment, creating one’s personal brand, marketing one’s personal brand, and evaluation and adjustment. In addition, the role digital media channels can play in the process is discussed.